Utilizing Pho’s Move in Composing Scientific Paper within AIMRD - Afi Ni’amah; Fabiola Dharmawanti Kurnia; Slamet Setiawan (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: Composing and publishing a scientific article needs compound responsibilities, mainly when Indonesian students write it since English is their foreign language. Swales pioneered CARS with three moves, followed by Pho, who mentions moves and steps in a research article using AIMRD, which can be worthy of consideration in composing a scientific article. Method: The moves and steps of undergraduate students’ research articles were analyzed qualitatively, using Pho’s moves and steps as parameters. The data analyzed consists of nine articles on English Education, seven on Applied Linguistics, and six on Applied Literature. Tables of move-analysis were prepared as the research instrument with different codes for classifying and analyzing the articles. Results: Undergraduate students place and develop moves along with steps effectively, which was inflicted by the thought patterns and the tendency of undergraduate students. Thus, writing research articles developed by undergraduate students could be considered in revising institution guides for composing research articles and reflection in composing research articles for other disciplines. Novelty: Most research on sections of research articles applying a move-based approach have worked with first language studies published in journals and focused on a particular section of the research article, while this study using Pho's moves and steps works with EFL learners, which compose an unpublished complete text of the scientific article. The findings of current research mediate both students' critical thinking and unfathomable argumentation skills by the availability manifestation of the rhetorical move. The main contribution of this research result is meant to alleviate writers, mainly undergraduate students, in generating research articles successfully.